Pengalaman Orang Tua dengan Anak yang Mengalami Hospitalisasi di Ruang Perawatan Anak Rumah Sakit Swasta Yogyakarta - Margareta Hesti Rahayu (I Care Jurnal Keperawatan STIKes Panti Rapih, 2020)
Background: When children are hospitalized, parents feel stressed. Fifty percent of parents have severe anxiety and 30% of parents experience panic when their child is first hospitalized. Objective: to explore parent’s experience with hospitalized children. Methods: This research is a qualitative descriptive study conducted at a private hospital in Yogyakarta. Data was collected in 2017. Participants in the study were selected using purposive sampling. This research instrument uses a questionnaire and interview guidelines. This research has received an ethical cleareance permit from the Ethics Committee of Ahmad Dahlan University. Data analysis use qualitative descriptive. Results: Emotional responses that arise in parents are sad, crying, anxiety, and worry, the emotional response of children is crying, fear, anxiety and the appearance of boredom, while the emotional response of siblings is anxiety and worry. The behavior and attitude of parents is to pray and try to be sincere and patient. Parents and nurses give support by providing opportunities for children to play and chat. Parents hope that their children can get well soon and get clear information about their child's condition. Conclusion: There are 4 theme in this research, emotional response, the parents behaviour and attitude, Support dan Parents hope. Keywords: parents expereince, children, hospitalized